Relationship between Degrees of Severity Gastroesophageal Reflux Disease (Gerd) with Quality of Life - Bulqaini, Alul Azmi; Darmadi (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background. Gastroesophageal reflux disease (GERD) is a pathological condition caused by the reflux of gastric contents into the esophagus, with symptoms that appear inside and outside the esophagus which can reduce the patient's quality of life. The aim study is to analyze the relationship between the severity of GERD and the quality of life of students Faculty of Medicine at Universitas Sumatera Utara (USU) in 2019 and 2020. Method. Cross-sectional research with a sampling technique in the form of total sampling. Data collection was carried out using an online questionnaire in the form of a Google form with an assessment using the GERD Questionnaire (GerdQ), Frequency scale for the symptoms of GERD (FSSG), Gastroesophageal reflux disease-health related quality of life questionnaire (GERD-HRQL), and the 20-item self-reporting questionnaire (SRQ-20). After that, the data that has been collected will be tabulated. This study used bivariate analysis, with the Chi-square test and the Fisher Exact Test. Results. The total number of samples that met the inclusion and exclusion criteria of the study was 225 people with 41 people with GERD (18.2%) suffering from GERD. Of the 41 Students of the Faculty of Medicine from USU in 2019 and 2020 with GERD, 29 people (70.7%) had a good quality of life, and the remaining 12 people (29.3%) had a bad quality of life. There is a relationship between GERD and gender and psychological stress. In addition, there is a relationship between quality of life and the severity of GERD, psychological stress, and drinking alcohol, but there is no relationship between quality of life and gender, smoking habits, and BMI. Conclusion. Most Medical School Students have a good quality of life, and there is a significant relationship between the severity of GERD and the quality of life.